The Influence Of Targeting And Relational Marketing On Customer Purchasing Decisions Cv. Putra Mas Pratama - Robin Robin; Devi Devi; Angeline Florencia (Digital Innovation : International Journal of Management, 2024)
The research conducted examined the influence of independent variables—targeting (X1) and relationship marketing (X2)—on the dependent variable, purchase decision (Y). The findings revealed that both targeting and relationship marketing individually have a positive and significant impact on customer purchase decisions at CV. Putramas Pratama Medan. Additionally, when considered together, targeting and relationship marketing significantly influence customer purchase decisions at the company. Based on these results, it is recommended that CV. Putramas Pratama should expand its target market to increase consumer responsiveness to the company's product offerings. Furthermore, the company should focus on building consumer trust by paying close attention to customer needs and feedback. This dual approach of broadening the target market and enhancing relationship marketing is expected to improve customer purchase decisions significantly.